Is Criminology & Public Policy "influential?": answers from altmetrics - Worrall, John L. (Criminology & public policy, 2022)
Research Summary We use an altmetric aggregator, the Altmetric Attention Score (AAS), to rank the influence of articles published in Criminology & Public Policy from the journal's inception through July 31, 2022. We also rank articles based on specific AAS components, namely, Twitter, news, and policy document mentions. Last, we regress AASs on article-level predictors, including research category, funding, open access type, and time since publication. With few exceptions, policing scholarship far outweighs other categories of research in terms of AAS-measured societal impact. Policy Implications In contrast to bibliometrics (e.g., citation counts), altmetrics measure scholarship's societal impact, including its influence on policy. Since Criminology & Public Policy was initially created with the intention of influencing crime-related policy, it is important to gauge the extent to which that has occurred. Other policy-oriented (or perhaps all) criminal justice/criminology journals should evaluate their influence via altmetrics.